In Their Own Words: Sexual Assault Resistance Strategies Among Kenyan Adolescent Girls Following Participation in an Empowerment Self-Defense Program - Edwards, Katie M. (Violence against women, 2024)
The purpose of this study was to examine, via testimonial data, resistance strategies used to thwart a sexual assault among slum-dwelling Kenyan adolescent girls (N = 678) following their participation in an empowerment self-defense program (IMpower). The majority (58.2%) of perpetrators were strangers; there were no differences in resistance strategies used between strangers versus known perpetrators (83.8% used verbal strategies, 33.2% used resistance strategies, 16.7% ran away, and 7.9% used distraction). Associations between resistance strategies and perpetrator tactics, number of assailants, location of the assault, and the presence of a bystander were also examined.